FORMATION OF SOFT SKILLS IN FUTURE PRACTICAL PSYCHOLOGISTS IN THE PROCESS OF STUDYING THE DISCIPLINE "MATHEMATICAL METHODS IN PSYCHOLOGY" - Mikheyeva, Tamara (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article highlights the peculiarities of the formation of Soft Skills of students-future practical psychologists. It is established that modern practical psychologists, in addition to professional qualities, should have well-developed social skills, such as the ability to generate new ideas (creativity), the ability to work in a team, sociability, and the ability to make informed decisions. The article describes the main methods and forms of teaching used in the process of studying the discipline "Mathematical Methods in Psychology" by students. The purpose of the article is to analyse the educational and professional programme "Practical Psychology" of the first (bachelor’s) level of higher education in the specialty 053 "Psychology" and the modern requirements of employers for practical psychologists. The task of research: to analyse the EPP "Practical Psychology" of the first (bachelor’s) level of higher education in the specialty 053 "Psychology"; to identify soft skills that psychologists should develop in order to be competitive in the labour market. To achieve this goal, the following research methods were used: scientific analysis, systematisation, generalisation, and comparison. The results of research. The study analysed the current requirements of employers for practical psychologists; identified soft skills (Soft Skills) that psychologists should have to be competitive in the labour market; presented examples of teaching methods and techniques used by the teacher to form general competencies in the process of teaching the discipline "Mathematical Methods in Psychology". Conclusions. Soft Skills that psychologists should have to be competitive in the labour market: communication skills, analytical skills, teamwork skills, problem-solving skills, organisational skills, flexibility and adaptability, etc. Teaching methods and techniques used by the teacher in the process of teaching the discipline "Mathematical Methods in Psychology": discussion, presentation, case-study, method of analogies, project method, small group work, creating a psychologically favourable atmosphere, method of creating a sense of success.